(3GdLdjS GdUGdM GdcGaj hGdCfjS GdfGUM GdTGais - (3GdeYdj Hf RcQjG GdgRhGfis
(3ChdgG (B:s
(3CeG HYO aEfi efP eOI eVJ hSfI NdJ acQJ ai CTjGA ef YLGFH Ndb Gddg hbO Ufa ai fMh gPG GdcJGH LeGYI ef Cgd GdYde hGdGOH cJGHkG Ydi CfMGA eNJdaI s
(3BNQgG (B:s
(3CMH ef GdfShGf cd bUhQI dgG fSH ai GdYGdejf bUjQ hef gPG GdfSH fSHI GdCfHjGA hGdQSd bO QaY GdYLGL HjJG aGOYfi HGSei EPG GdCfSGH WGdJ jcafi Je GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3Hg (B23 (3eLdSkG abW ef GdChds
(3HBNQg eWGdYI HGSe eMeO CHh RjO Hf YHO GdZfis
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdCOHs